Mongolia Quarterly Economic Update, October 2011 - World Bank (World Bank, Washington, DC, 2017)
The economic rebound in recent quarters has been stronger than expected and the economy is showing signs of overheating. These signs are show up in rising inflation, especially of those goods and services which are in strong demand, but cannot easily be imported or whose local supply cannot readily be increased to meet the growing demand. Gross Domestic Product (GDP) growth reached 20.8 percent year-on-year (yoy) in Q3, following an outturn of 17.3 percent in Q2. Growth for the year as a whole will likely hit 15 percent, if not more, up from 6.4 percent in 2010, and is being pushed by infrastructure spending as Mongolia develops its vast mineral wealth. Inflation continues its upward trend. The trade deficit is close to record levels (US$ 1.4 bn in September using 12-month rolling sums) driven by a surge in mining-related equipment and fuel imports. Exports are growing strongly too, driven by large coal shipments to China. The 2012 budget continues this fiscal expansion and targets a 74 percent increase in expenditures (mostly on wages and social transfers).